Correlation of lipid profile, glucose, and body composition on insulin resistance in overweight and obese subjects - Fatmayanti Nawai; Ahmad Syauqy; Adriyan Pramono (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Indonesia has the highest prevalence of obesity in the Asia-Pacific region. Insulin resistance is a form of obesity that causes damage to the liver, heart, and pancreatic tissue as we age. This study aimed to determine the correlation among lipid profiles, glucose levels, body composition, and insulin resistance. Methods: This study used a pre-experimental design and was conducted at the Gorontalo Ministry of Health Polytechnic in February 2023 on 31 obese people whose venous blood was collected for examination of insulin resistance variables. Data were collected by purposive sampling with data analysis using Pearson Correlation and Spearman Rank statistical tests at a 95% confidence interval (CI). Results: Insulin resistance status based on sex, using the TyG index, was dominated by women (55%) among the 20 people who experienced insulin resistance. Men are more likely to be aged <30 years than women, according to the HOMA-IR index. The Pearson triglyceride test value (p= 0,000, r= 0,974) shows that the relationship between triglycerides and the TyG index was very strong, whereas when the HOMA-IR index was used, fasting insulin (p= 0,000, r= 0,985) had a very strong relationship. In conclusion, lipid profile (triglycerides, total cholesterol, LDL), fasting glucose, fasting insulin, and visceral fat percentage correlated with insulin resistance.